New directions in public opinion - Adam J. Berinsky (New directions in American politics, 2012)
New Directions in Public Opinion brings together leading scholars to provide an accessible and coherent overview of the current state of the field of public opinion. Each chapter provides a general overview of topics that are at the cutting edge of study as well as well-established cornerstones of the field. Suitable for use as a main textbook or in tandem with a lengthier survey, it comprehensively covers the topics of public opinion research and pushes students further to explore critical topics in contemporary politics.